2022
DOI: 10.37945/cbr.2022.09.07
|View full text |Cite
|
Sign up to set email alerts
|

How Banks Can Leverage Credit Risk Evaluation to Improve Financial Performance

Abstract: The research aims to examine the impact of credit risk evaluation on the financial performance of American and European commercial banks during the period 2017-2021. A set of 37 commercial banks were selected to represent the entire banking industry of those two continents. To measure this relationship, two mathematical models were created. Research has revealed that credit risk evaluation influences the financial performance of the American and European commercial banks as represented by ROE and ROA. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Besides the accessibility of information, the development of computational power as well as ease of use of BDA solutions have helped businesses to automate the decision-making process of theirs using Artificial Intelligence strategies. Thus, the investments running a business Intelligence technologies greatly enhance the online business functionality of businesses through predictive and prescriptive analysis using BDA [7]. Nevertheless, present scientific studies revealed that these investments might boost business efficiency just in case they're integrated into the decision making processes.…”
Section: Literature Reviewmentioning
confidence: 89%
See 1 more Smart Citation
“…Besides the accessibility of information, the development of computational power as well as ease of use of BDA solutions have helped businesses to automate the decision-making process of theirs using Artificial Intelligence strategies. Thus, the investments running a business Intelligence technologies greatly enhance the online business functionality of businesses through predictive and prescriptive analysis using BDA [7]. Nevertheless, present scientific studies revealed that these investments might boost business efficiency just in case they're integrated into the decision making processes.…”
Section: Literature Reviewmentioning
confidence: 89%
“…Sazu & Jahan (2022) believed export demand elasticities in developing and manufacturing places by time series methods [6]. Sazu and Jahan (2022) forecasted seaborne trade passes of 4 various commodity solutions by utilizing Vector Auto Regression [7]. Sazu investigated seasonality in Pakistan's merchandise exports as well as imports by making use of a univariate ARIMA design [8].…”
Section: Literature Reviewmentioning
confidence: 99%
“…On September 2021 we sent a questionnaire to a sample of 1,394 BDC professionals accredited by the French Ministry of Economic Development, who had considerable expertise in the layout and implementation of BDC tasks within organizations and companies. We shipped the questionnaire to empirically verify the theoretical framework suggested by Isenberg et al (2022). Just before delivering the last questionnaire, a double validation procedure was performed.…”
Section: Machine Developmentmentioning
confidence: 99%
“…Originating from research involving 707 executives, the Economist Intelligence Unit accounts that management decisions based strictly on instinct or maybe knowledge are frequently viewed as suspect which such choices are frequently dependent on' hard analytic information'. On the opposite hand, the analysis by suggests that businesses lack organized information for decision support, a widespread information tradition as well as competent analysts [9]. With reference to steps three as well as four, On Line Analytical Process programs have increased the information analysis, visualization and reporting potential.…”
Section: Literature Reviewmentioning
confidence: 99%